Pengendalian kualitas base oil menggunakan metode six sigma - Achmad Bahauddin; Muhammad Ridho Latif (Journal Industrial Servicess, 2022)
Production quality is one of the factors that can be a source of company excellence to achieve efficiency and effectiveness in running its business. Good production quality can increase company competitiveness and consumer confidence, so that profits can also increase. PT ABC is one of the companies engaged in the processing of hazardous (B3) waste. The problems faced by PT ABC is the percentage of defects in base oil products which is still quite high at 57.79%, so improvements are needed in order to reduce the percentage of defects. This study aims to determine the critical to quality (CTQ) in the production of base oil at PT ABC, determine the value of sigma on base oil production at PT ABC, as well as providing suggestions for improvements to improve the production process at PT ABC. This research was conducted using the six sigma method using the DMAIC approach (Define, Measure, Analyze, Improve, and Control). Based on the results of data processing obtained 6 criteria critical to quality (CTQ) in the production of base oil at PT ABC where the criteria for mixing the bleaching earth agent is not evenly distributed gets the highest score. The sigma value obtained in the production of base oil at PT ABC is 2,859 and can be classified as the industry average in Indonesia.